Direct Interaction Between CD163 N-Terminal Domain and MYH9 C-Terminal Domain Contributes to Porcine Reproductive and Respiratory Syndrome Virus Internalization by Permissive Cells - Hou, Gaopeng; Xue, Biyun; Li, Liangliang; Nan, Yuchen; Zhang, Lu; Li, Kuokuo; Zhao, Qin; Hiscox, Julian A.; Stewart, James P.; Wu, Chunyan; Wang, Jingfei; Zhou, En-Min (Frontiers in Microbiology, 2019)
Porcine reproductive and respiratory syndrome virus (PRRSV) has a highly restricted tropism for cells of the monocyte-macrophage lineage, including porcine alveolar macrophages (PAMs). PRRSV entry into permissive cells involves several mediators in addition to two required host cell receptors, CD163 and MYH9. It is unknown whether CD163 directly interacts and/or cooperates with MYH9 to facilitate PRRSV infection. In this study, CD163 and MYH9 were co-immunoprecipitated from PAMs regardless of PRRSV infection status. Further truncation analysis indicated that the CD163 N-terminal region, containing scavenger receptor cysteine-rich domains 1 to 4 (SRCR1-4), directly interacts with the MYH9 C-terminal domain region without involvement of other adaptor proteins. Meanwhile, nonpermissive HEK293T cells that stably expressed truncated swine CD163 SRCR1-4 domain did not support virus attachment; however, virus attachment to cells stably expressing SRCR5-CT domain was demonstrated to occur without appreciable virus internalization. The involvement of the SRCR1-4 domain in virus internalization was further demonstrated by the fact that incubation of recombinant SRCR1-4 protein with PAMs abolished subsequent virus internalization by permissive cells. Thus, these results collectively demonstrate that CD163 SRCR1-4 interacts with the MYH9 C–terminal domain to facilitate PRRSV virion internalization by permissive cells, thus expanding our understanding of PRRSV cell-invasion mechanisms.